91.6% efficient hybrid DC-DC buck converter with wide programmable conversion range. (August 2021) - Safwat, Mohamed; Ibrahim, Sameh
Abstract: A new power-efficient and wide input range hybrid dc-dc buck regulator is proposed in this paper. The proposed regulator could be used in different applications that needs power and area efficient switching regulators like battery chargers, IoT, wearable and hearable technologies. This regulator employs an inductor positioned at the lower current path to reduce the DC component of the inductor current. This significantly decreases inductor losses. The inductor is followed by a switched capacitor circuit used to deploy the step-down function despite the inductor position. Detailed analysis of the proposed regulator architecture with emphasis on the efficiency, power density, and output ripples are presented and verified by simulations. The proposed converter regulates an output voltage of 650 mV for an input voltage range of 0.75–1.8 V. The regulator can achieve peak efficiency of 91.6%, supplies a maximum load current of 0.5 A and is implemented using 0.18 μ m CMOS technology.